A compassion framework: the role of compassion in schools in promoting well-being and supporting the social and emotional development of children and young people. (3rd July 2018) - Al-Ghabban, Ammar
ABSTRACT: Our current social and political context is awash with pronouncements about the growing number of children and young people with mental health issues. This paper explores how school culture that is founded upon a compassion framework is well placed to support the promotion of pupils' mental health and well-being. Drawing upon experiences of being a senior leader in a specialist social, emotional and mental health (SEMH) educational setting and of supporting a wide range of mainstream schools in the area of SEMH and well-being, this paper outlines some of the conflicting interests and ubiquitous tensions that present challenges in the contemporary UK education system. Conceptualisations of compassion and other relevant theoretical perspectives are referred to in order to illustrate how the, often, at times, competing needs of different constituencies (pupils, teaching and non-teaching staff, management, parents and carers) within school communities are best served when disentangled from each other and addressed with attention and clarity.